2007
DOI: 10.1038/sj.mp.4002051
|View full text |Cite
|
Sign up to set email alerts
|

Association study of CSF2RB with schizophrenia in Irish family and case – control samples

Abstract: Colony stimulating factor 2 receptor, beta (CSF2RB) is the shared subunit of receptors for interleukin 3 (IL3), colony stimulating factor 2 (CSF2) and IL5, and is responsible for the initiation of signal transduction triggered by ligand binding. In our previous study, we showed the evidence that the IL3 gene is associated with schizophrenia and the associations observed are sex-specific and dependent on family history (FH). In this article, we studied 10 singlenucleotide polymorphisms in the CSF2RB gene in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…al. found rs1859427 and rs6861170 to be significantly associated with schizophrenia within their case-control population, and significance was maintained even after correction for multiple testing (p=0.01967 for both markers) (Chen et al, 2008). The MAF for both rs1859427 and rs6861170 FBXL21 markers were very similar in the schizophrenia group for both the present study (MAF=0.32 for both markers) and in the Chen et.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…al. found rs1859427 and rs6861170 to be significantly associated with schizophrenia within their case-control population, and significance was maintained even after correction for multiple testing (p=0.01967 for both markers) (Chen et al, 2008). The MAF for both rs1859427 and rs6861170 FBXL21 markers were very similar in the schizophrenia group for both the present study (MAF=0.32 for both markers) and in the Chen et.…”
Section: Discussionsupporting
confidence: 64%
“…The p53 pathway plays an essential role in the modulation of neurodevelopmental processes (including cerebral vascularization and neurogenesis) and/or to neurodevelopmental disorders such as schizophrenia. Due to their previous association in different reports and populations (Chen et al, 2008;Middleton et al, 2002), we analyzed a set of potential Single Nucleotide Polymorphisms (SNPs) in the UBE2D1 (coding for E2D1 protein), PIAS2…”
Section: Introductionmentioning
confidence: 99%
“…One of these directions is associated with the activity of the immune system and its effects on neural plasticity, glial activation and eventually the associated functional disorders of CNS. In this regard several studies for genetic associations with schizophrenia a linkage is found with components of the IL-3 signaling pathway -the gene coding for IL-3 (3) and the genes coding for the two subunits of the IL-3 receptor (4,11) In 2008 Akemi Hoshino è Hodaka Fujii(10) identified the gene CCDC86 to be directly induced by IL-3 in a IL-3 dependent pro-B cell line (14 ) and named it Ñyclon (cytokine induced protein with coiled-coil domain) (10). In a consequent study the gene was identified to be important for the phenomenon of activation induced cell death (AICD) in T lymphocytes (14).…”
mentioning
confidence: 99%
“…CSF2RB which regulates both IL3 and CSF2, was associated with schizophrenia. 35,40 CSF2 has also been associated with numerous autoimmune disorders and inflammation. [41][42] The IRF1 gene activates other interferons and is associated with inflammatory conditions 43 and with fibrinogen.…”
mentioning
confidence: 99%
“…33 The ACSL6 gene has been linked to schizophrenia 32 and an animal model of depression. 34 Interleukin 3 (IL3) is a cytokine with neurotrophic activity; it has been associated with schizophrenia, 35 but also several inflammatory conditions, including asthma and…”
mentioning
confidence: 99%